Discovering chemistry with natural bond orbitals - Weinhold, Frank, 1941-; Landis, Clark R., 1956- (Hoboken, NJ : Wiley, 2012)
"This book is about chemical bonds, their intrinsic energies and the corresponding dissociation energies which are relevant in reactivity problems; it is the first book to detail relatively uncomplicated but physically meaningful approaches to molecular properties, an area important to help understand chemical principles and predict chemical properties. The primary goal of this book is to enable students to gain proficiency in using the NBO program to re-express complex many-electron wavefunctions in terms of intuitive chemical concepts and orbital imagery, with minimal distractions from underlying mathematical or programming details"--
Discovering Chemistry with Natural Bond Orbitals; Contents; Preface; 1 Getting Started; 1.1 Talking to your electronic structure system; 1.2 Helpful tools; 1.3 General NBO keylist usage; 1.4 Producing orbital imagery; Problems and exercises; 2 Electrons in Atoms; 2.1 Finding the electrons in atomic wavefunctions; 2.2 Atomic orbitals and their graphical representation; 2.3 Atomic electron configurations; 2.4 How to find electronic orbitals and configurations in NBO output; 2.5 Natural atomic orbitals and the natural minimal basis; Problems and exercises; 3 Atoms in Molecules.
Includes index.
Machine generated contents note: Preface 1 Getting Started1.1 Talking to your electronic structure system1.2 Helpful tools1.3 General $NBO keylist usage1.4 Producing orbital imageryProblems and Exercises2 Electrons in Atoms2.1 Finding the electrons in atomic wavefunctions2.2 Atomic orbitals and their graphical representation2.3 Atomic electron configurations2.4 How to find electronic orbitals and configurations in NBO output2.5 Natural Atomic Orbitals and the Natural Minimal BasisProblems and Exercises3 Atoms in Molecules3.1 Atomic orbitals in molecules3.2 Atomic configurations and atomic charges in molecules3.3 Atoms in open-shell moleculesProblems and Exercises4 Hybrids and Bonds in Molecules4.1 Bonds and lone pairs in molecules4.2 Atomic hybrids and bonding geometry4.3 Bond polarity, electronegativity, and Bent's rule4.4 Electron-deficient 3-center bonds4.5 Open-shell Lewis structures4.6 Lewis-like structures in transition metal bondingProblems and Exercises5 Resonance Delocalization Corrections5.1 The Natural Lewis Structure perturbative model5.2 2nd-order perturbative analysis of donor-acceptor interactions5.3 $DEL energetic analysis5.4 Delocalization tails of Natural Localized Molecular Orbitals5.5 How to $CHOOSE alternative Lewis structures5.6 Natural Resonance TheoryProblems and Exercises6 Steric and Electrostatic Effects6.1 Nature and evaluation of steric interactions6.2 Electrostatic and dipolar analysisProblems and Exercises7 Nuclear and Electronic Spin Effects7.1 NMR chemical shielding analysis7.2 NMR J-coupling analysis7.3 ESR spin-density distributionProblems and Exercises8 Coordination and Hyperbonding8.1 Lewis acid-base complexes8.2 Transition metal coordinate bonding8.3 Three-center, four-electron hyperbondingProblems and Exercises9 Intermolecular Interactions9.1 Hydrogen-bonded complexes9.2 Other donor-acceptor complexes9.3 Natural energy decomposition analysisProblems and Exercises10 Transition State Species and Chemical Reactions10.1 Ambivalent Lewis structures: the transition-state limit10.2 Example: bimolecular formation of formaldehyde10.3 Example: unimolecular isomerization of formaldehyde10.4 Example: SN2 halide exchange reactionProblems and Exercises11 Excited State Chemistry11.1 Getting to the "root" of the problem11.2 Illustrative applications to NO excitations11.3 Finding common ground: state-to-state NBO transferability11.4 NBO/NRT description of excited state structure and reactivity11.5 Conical intersections and intersystem crossingsProblems and ExercisesAppendix A: What's Under the Hood?Appendix B: Orbital Graphics: The NBOView Orbital PlotterAppendix C: Digging at the DetailsAppendix D: What if Something Goes Wrong?Appendix E: Atomic Units and Conversion Factors.
Print version record.
Keywords: Chemical bonds; Molecular orbitals; SCIENCE -- Chemistry -- Physical & Theoretical; Chemical bonds; Molecular orbitals; Electronic books